2010
DOI: 10.1016/j.neuron.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Response Features of Parvalbumin-Expressing Interneurons Suggest Precise Roles for Subtypes of Inhibition in Visual Cortex

Abstract: Summary Inhibitory interneurons in the cerebral cortex include a vast array of subtypes, varying in their molecular signatures, electrophysiological properties, and connectivity patterns. This diversity suggests that individual inhibitory classes have unique roles in cortical circuits; however, their characterization to date has been limited to broad classifications including many subtypes. We used the Cre/LoxP system, specifically labeling parvalbumin(PV)-expressing interneurons in visual cortex of PV-Cre mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
198
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(226 citation statements)
references
References 68 publications
18
198
2
Order By: Relevance
“…3-6), showing a weak tuning for orientation and complex-like responses. These results are consistent with studies of the responses of fast-spiking cells (Niell and Stryker, 2008) and parvalbuminpositive neurons (Sohya et al, 2007;Kerlin et al, 2010;Liu et al, 2010;Ma et al, 2010;Zariwala et al, 2011) in mouse visual cortex but do not exclude the possibility that distinct subpopulations of GABAergic neurons may have more diverse properties (Ma et al, 2010;Runyan et al, 2010).…”
Section: Functional Diversity Of Local Visual Cortical Populationssupporting
confidence: 72%
See 1 more Smart Citation
“…3-6), showing a weak tuning for orientation and complex-like responses. These results are consistent with studies of the responses of fast-spiking cells (Niell and Stryker, 2008) and parvalbuminpositive neurons (Sohya et al, 2007;Kerlin et al, 2010;Liu et al, 2010;Ma et al, 2010;Zariwala et al, 2011) in mouse visual cortex but do not exclude the possibility that distinct subpopulations of GABAergic neurons may have more diverse properties (Ma et al, 2010;Runyan et al, 2010).…”
Section: Functional Diversity Of Local Visual Cortical Populationssupporting
confidence: 72%
“…3A1), while responses of inhibitory neurons were nonselective or weakly selective (Fig. 3A2) (but see Ma et al, 2010;Runyan et al, 2010). We quantified response selectivity with a tuning index whose value ranges from 0, for not tuned, to 1, for highly tuned (see Materials and Methods).…”
Section: Spatial Summation In Excitatory and Inhibitory Neuronsmentioning
confidence: 99%
“…The response gain of neurons in the visual cortex is under the control of GABA(A) mediated inhibition (Liu et al, 2010;Katzner et al, 2011), associated to PV-containing interneurons (Atallah et al, 2012;Runyan et al, 2010). We have observed that the lack of PV does indeed significantly increase the firing rate of neurons of the visual cortex in the absence as well as in the presence of a visual stimulation.…”
Section: Discussionmentioning
confidence: 82%
“…It is possible that pyramidal cell activity is somehow modified in the PVKO mice because of the major role played by PV-expressing cortical interneurons on the shaping of the pyramidal cell output in WT animal (Runyan et al 2010;Atallah et al 2012). However, only a stimulation paradigm associated to simultaneous recordings in the cortex and in RTN could provide some answers to that question.…”
Section: Functional Connectivity Of Rtn Neurons Is Unchanged In Pvko mentioning
confidence: 99%